2013
DOI: 10.7314/apjcp.2013.14.9.5301
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Clinical Behavior of Laryngeal Squamous Cell Carcinomas and Expression of VEGF, MMP-9 and E-Cadherin

Abstract: The biological mechanisms of cancer and associations with behavior of tumours need to be studied to understand progression and determine appropriate treatments. Here we investigated expression of VEGF, MMP-9 and E-cadherin in laryngeal SCCs and their relations with clinical behavior. This prospective study was based on 38 surgical specimens from patients with primary laryngeal SCC and data recorded in their cards. Expression of the three factors in tumor tissue was examined using immunohistochemistry and corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
(57 reference statements)
4
13
1
Order By: Relevance
“…Many studies have demonstrated that MMP-9 (Hassan et al, 2012;Zhang et al, 2012;Akdeniz et al, 2013;Asuthkar et al, 2013;Darakhshan et al, 2013;Li et al, 2013), ERK1/2 (Romano et al, 2012), KIT (Kim et al, 2011) and PTEN are considered to be the potential targeted genes of miR-494. In present study, BAG-1 is predicted as the targeted gene of miR-494 by using bioinformatics tools TargetScan, PicTar, and Miranda.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that MMP-9 (Hassan et al, 2012;Zhang et al, 2012;Akdeniz et al, 2013;Asuthkar et al, 2013;Darakhshan et al, 2013;Li et al, 2013), ERK1/2 (Romano et al, 2012), KIT (Kim et al, 2011) and PTEN are considered to be the potential targeted genes of miR-494. In present study, BAG-1 is predicted as the targeted gene of miR-494 by using bioinformatics tools TargetScan, PicTar, and Miranda.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is a multifunctional cytokine that exerts a variety of effects on vascular endothelial cells that together promote the formation of new blood vessels, increases vascular endothelial permeability, stimulates the proliferation of endothelial cells and promote cancer cell progression (Dvorak, 2002;Mohammed et al, 2007;Niu et al, 2010;Akdeniz et al, 2013;Huang et al, 2013;Zhang et al, 2013). In particular, serum VEGF-A levels are elevated in patients with HNSCC compared to healthy controls (De Schutter et al, 2005;Hong et al, 2009;Liang et al, 2013).…”
Section: Serum Vascular Endothelial Growth Factor-a (Vegf-a) As a Biomentioning
confidence: 99%
“…The tumoral involvement of the cartilage is thought to be promoted by the chemotactic effect of vascular endothelial growth factor. 19 The ossification of the thyroid cartilage is another reason for cartilage involvement. The ossification of the ITC occurs in front of the LTC due to the insertion, the pulling from the vocal muscles, and the cartilage angle.…”
Section: Discussionmentioning
confidence: 99%